Peran Kecerdasan Buatan (Artificial Intelligence) dalam Mengubah Pola Belajar Siswa di SDN 82 Kota Bengkulu - Salma Napiah; Agnes Tri Muryati; Hengki Satrisno; Dalima Septiria (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
This study aims to describe the role of Artificial Intelligence (AI) in transforming students' learning patterns at SDN 82 Bengkulu City. The study employed a qualitative approach using a descriptive research design. The research participants consisted of the principal, teachers, and students, who were selected through purposive sampling. Data were collected through observations, interviews, and documentation, while the data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Artificial Intelligence (AI) serves as a supportive learning medium that helps students access information, understand learning materials, and complete academic tasks more effectively. The use of AI has also transformed students' learning patterns, making them more active, independent, adaptive, and flexible, as they are no longer solely dependent on textbooks or teachers' explanations as their primary sources of learning. However, the implementation of AI still faces several challenges, including limited digital literacy, inadequate facilities and infrastructure, and the potential for excessive dependence on technology if not accompanied by proper teacher guidance. Therefore, the effective integration of AI into the learning process should be supported by improving both teachers' and students' competencies to ensure high-quality learning that is aligned with technological advancements in the digital era.